1994
DOI: 10.1111/j.1476-5381.1994.tb14796.x
|View full text |Cite
|
Sign up to set email alerts
|

Class I and III antiarrhythmic actions of prazosin in guinea‐pig papillary muscles

Abstract: 1 The electrophysiological effects of prazosin, a highly specific ax-adrenoceptor antagonist, on transmembrane action potential characteristics were studied in guinea-pig papillary muscles. 2 At concentrations between 10-6 M and 10-5 M, prazosin produced a concentration-dependent decrease in the maximum upstroke velocity (V,,,.) and a progressive lengthening of the action potential duration at 50% (APDm) and 90% (APD90) of repolarization. The prolongation of the APD5o and APD91 values was independent of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…An importance of these effects can be clearly ruled out for this study, since the model uses isolated buffer perfused hearts and therefore avoids humoral or systemic interferences. Furthermore, it has been suggested that direct membrane stabilizing actions similar to those of class I antiarrhythmic agents account for the antifibrillatory effect of phentolamine (Rosen et al 1971), a non-specific effect, which has also been demonstrated for prazosin (Northover 1983;Perez et al 1994). As this argument cannot be clearly ruled out in our investigation, we evaluated further alpha-adrenoceptor antagonists, such as WB 4101.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…An importance of these effects can be clearly ruled out for this study, since the model uses isolated buffer perfused hearts and therefore avoids humoral or systemic interferences. Furthermore, it has been suggested that direct membrane stabilizing actions similar to those of class I antiarrhythmic agents account for the antifibrillatory effect of phentolamine (Rosen et al 1971), a non-specific effect, which has also been demonstrated for prazosin (Northover 1983;Perez et al 1994). As this argument cannot be clearly ruled out in our investigation, we evaluated further alpha-adrenoceptor antagonists, such as WB 4101.…”
Section: Discussionmentioning
confidence: 94%
“…The alphaadrenoceptor antagonist prazosin, however, failed to alter ischemia-induced arrhythmias in anesthetized open-chest canine preparations (Bolli et al 1984). These equivocal results may be due to ancillary properties of adrenoceptor antagonists such as class I and III actions (Perez et al 1994), and to the use of different models in which indirect actions of the compounds such as central-neuronal, humoral, and systemic vascular effects were of varying importance.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between V max and the resting membrane potential from which the action potential was elicited was studied in papillary muscles driven at 0.05 Hz. The resting membrane potential was depolarized by increasing in a step‐wise manner the extracellular K + concentration, [K + ] o , from 2 to 16 mM (Pérez et al , 1994) and the V max was measured after the resting membrane potential had reached a steady‐state at each [K + ] o .…”
Section: Methodsmentioning
confidence: 99%
“…Under these conditions, the fast inward Na + current was voltage‐inactivated and excitability, i.e. slow action potentials, was restored in depolarized muscles driven at 0.1 Hz by adding isoprenaline(10 −6 m) to the perfusate (Pérez et al , 1994). After control values for each parameter had been obtained, incremental concentrations of each drug were added to the bath to obtain a complete concentration‐response curve.…”
Section: Methodsmentioning
confidence: 99%
“…Prazosin has been demonstrated to exibit a protective effect on myocardial ischaemic injury [82]. It is known that prazosin has a Na + channel blocking action as well as an α I -adrenoceptor blocking action [83]. Reactive oxygen causes excessive Na + entry through the fast Ca 2+ channel, leading to intracellular Ca 2+ overload through the Na + -Ca 2+ exchange system, and hence myocardial damage [84].…”
Section: Prazosin Attenuate •Oh Generationmentioning
confidence: 99%